Luteolin-7-O-β-d-glucuronide Ameliorates Cerebral Ischemic Injury: Involvement of RIP3/MLKL Signaling Pathway - Xing Fan; Fang Lin; Yu Chen; Yuling Dou; Ting Li; Xinxin Jin; Jintao Song; Fang Wang (Molecules, 2024)
Luteolin-7-O-β-d-glucuronide (LGU) is a major active flavonoid glycoside compound that is extracted from Ixeris sonchifolia (Bge.) Hance, and it is a Chinese medicinal herb mainly used for the treatment of coronary heart disease, angina pectoris, cerebral infarction, etc. In the present study, the neuroprotective effect of LGU was investigated in an oxygen glucose deprivation (OGD) model and a middle cerebral artery occlusion (MCAO) rat model. In vitro, LGU was found to effectively improve the OGD-induced decrease in neuronal viability and increase in neuronal death by a 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and a lactate dehydrogenase (LDH) leakage rate assay, respectively. LGU was also found to inhibit OGD-induced intracellular Ca2+ overload, adenosine triphosphate (ATP) depletion, and mitochondrial membrane potential (MMP) decrease. By Western blotting analysis, LGU significantly inhibited the OGD-induced increase in expressions of receptor-interacting serine/threonine-protein kinase 3 (RIP3) and mixed lineage kinase domain-like protein (MLKL). Moreover, molecular docking analysis showed that LGU might bind to RIP3 more stably and firmly than the RIP3 inhibitor GSK872. Immunofluorescence combined with confocal laser analyses disclosed that LGU inhibited the aggregation of MLKL to the nucleus. Our results suggest that LGU ameliorates OGD-induced rat primary cortical neuronal injury via the regulation of the RIP3/MLKL signaling pathway in vitro. In vivo, LGU was proven, for the first time, to protect the cerebral ischemia in a rat middle cerebral artery occlusion (MCAO) model, as shown by improved neurological deficit scores, infarction volume rate, and brain water content rate. The present study provides new insights into the therapeutic potential of LGU in cerebral ischemia.